Loss of plasticity in life‐history strategy associated with secondary invasion into stressful environments in invasive narrowleaf plantain (Plantago lanceolata L.). (24th March 2018) - Wan, Justin S. H.; Fazlioglu, Fatih; Bonser, Stephen P.
Abstract: Adaptation to changing environments is a fundamental process occurring throughout a species' range, particularly under novel and stressful conditions at the range‐edges of invasive species. However, the evolutionary consequences associated with adaptation are still poorly understood. Secondary invasion into stressful areas may incur fitness costs that could limit range expansion. In addition, developmental plasticity is predicted to be lost under strong selection in stressful habitats. We assessed populations across a range transect of an invasive plant ( Plantago lanceolata L.) for a loss of developmental plasticity and for adaptation costs, where there was prior expansion inland into stressful and novel areas from relatively benign areas closer to the coast. In the glasshouse, we grew plants from seed originating from two secondary invasion locations (near‐edge and edge), and from the range centre location representing the area of primary invasion. Plants were exposed to high or low nutrient treatment, and novel copper stress and control (no copper) treatment to assess adaptation costs associated with secondary invasion. In addition, we compared the costs in near‐edge and edge plants. Developmental plasticity in life‐history traits was lost for secondary invasion plants compared to plants from the range centre. Plants from secondary invasion locations expressed a slower life‐history under both nutrient treatments. In contrast, range‐centre plants were able to switch to a faster life‐history under high nutrient treatment. Our copper treatment had only slight effects on plants, where they expressed intermediate specific leaf area (SLA) under copper treatment. Near‐edge plants had the lowest plant size and reproduction. The loss of plasticity associated with secondary invasion may have implications on evolution in range‐edge populations. Phenotypic plasticity may have initially mediated ecological adaptation to stressful habitats; however, adaptation to stressful conditions can also have the consequence of inhibiting further range expansion in invasive species.